UPAYA PENGEMBANGAN KEMANDIRIAN EKONOMI PESANTREN (Studi Kasus Di Pondok Tahfidz Qur'an Al-Hasanah Bandung) - Denur Azharudin; Imam Sopingi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Whether we realize it or not, financial problems often threaten the existence of pesantren. The purpose of this study was to determine the efforts of Pondok Tahfidz Qur'an Al-Hasanah Bandung in utilizing its potential for economic development and to find out the efforts made in realizing the economic independence of Islamic Boarding Schools. This study uses a qualitative method with a case study approach according to Robet K. Yin, with data analysis using the Al-Qur'an and Al-Hadith. The results of this study indicate that the development process is carried out by analyzing the potential possessed by Islamic boarding schools, strengthening the resources they have, and involving students and local communities to participate in the development process. Processing agricultural products to meet the daily needs of students, forming business entities and other supporting media for marketing the products produced so that the results of these efforts can meet the operational costs of Islamic boarding schools.